Selected WTO Rules and Some Implications for Fund Policy Advice - Buchs, Thierry (IMF Working Papers; Working Paper, 1996)
The paper surveys six WTO agreements selected on the basis of their potential relevance for Fund-supported programs, namely Customs Valuation, Subsidies, Safeguards, Antidumping, Trade-Related Investment Measures, and Trade in Services. It offers a critical reading of the rules, and highlights potential issues of concern for the Fund in its policy dialogue with member countries with selected country examples. As some rules have very different implications for various groupings of countries, the paper calls attention to policy consistency in the trade area of these countries, and points out some areas where implementation of the rules might pose problems.